The manuscript from the Museum of the national cultures in Iwye and the other manuscripts written with the non-Arabic script by the Tatars of the former Grand Duchy of Lithuania - Synkova, Irina; Tarelko, Michail (Slavistica Vilnensis, 2016)
The Tatar manuscript written in Cyrillic is kept in the Museum of the national cultures in Iwye (Belarus). The manuscript dates from the second part of the 20th century. It contains some stories on the Biblical and Quranic topics (about the kings David and Solomon). The article talks about the beginning and evolution of the Cyrillic and Latin writing among the Tatars of the former Grand Duchy of Lithuania. The authors of the article also attempt to determine the place of the researched document in this tradition. The considerable attention is paid to the determination of the genre affiliation of the texts (stories) that are in this manuscript and to the problem of identification of the sources used in it.